2014
DOI: 10.1001/jama.2014.7586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postoperative Antibiotic Administration on Postoperative Infection Following Cholecystectomy for Acute Calculous Cholecystitis

Abstract: clinicaltrials.gov Identifier: NCT01015417.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 26 publications
(26 reference statements)
1
114
0
8
Order By: Relevance
“…Full texts of 63 articles were reviewed and assessed for eligibility, and 34 studies including 28 RCTs and 3 prospective and 3 retrospective trials were included in this meta-analysis. Twenty-nine full-text articles555657585960616263646566676869707172737475767778798081828384 were excluded because of the following reasons: inclusion criteria not met,83 inappropriate intervention,5557707784 inappropriate comparator,565859 insufficient data reported, 606163656667686971727374757678808182 and data duplication 6264. The procedure for the study selection is summarized in the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts of 63 articles were reviewed and assessed for eligibility, and 34 studies including 28 RCTs and 3 prospective and 3 retrospective trials were included in this meta-analysis. Twenty-nine full-text articles555657585960616263646566676869707172737475767778798081828384 were excluded because of the following reasons: inclusion criteria not met,83 inappropriate intervention,5557707784 inappropriate comparator,565859 insufficient data reported, 606163656667686971727374757678808182 and data duplication 6264. The procedure for the study selection is summarized in the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In an observational study of 287 patients with moderate acute cholecystitis, antibiotic treatment for 4 days after early cholecystectomy did not decrease the incidence of surgical site infections when compared to patients who received antibiotics postoperatively for 0 to 4 days [59]. In an RCT of 414 patients, after early laparoscopic cholecystectomy for mild or moderate acute cholecystitis, lack of postoperative antibiotics did not result in a greater incidence of postoperative infections compared to patients who received antibiotics postoperatively for 5 days [28]. Trial evidence and expert opinion suggest there is no benefit in continuing antibiotics beyond 24 h after cholecystectomy for uncomplicated acute cholecystitis.…”
Section: The Use Of Antibiotics In Acute Cholecystitismentioning
confidence: 90%
“…Most studies found that post operative antibiotic administration did not reduce the incidence of SSI compared to patients who received placebo on the post operative period [17,18]. A study involving patients undergoing renal transplant showed that a single dose of appropriate antibiotic agent was as good as multiple doses especially in patients with no additional co-morbidities [19].…”
Section: What Is the Optimal Timing Of Antibiotic Prophylaxis In Surgmentioning
confidence: 99%